2011
DOI: 10.3389/fcimb.2011.00001
|View full text |Cite
|
Sign up to set email alerts
|

Non-Typeable Haemophilus influenzae Invasion and Persistence in the Human Respiratory Tract

Abstract: Non-typeable Haemophilus influenzae (NTHI) is an opportunistic bacterial pathogen of the human respiratory tract and is a leading cause of respiratory infections in children and adults. NTHI is considered to be an extracellular pathogen, but has consistently been observed within and between human respiratory epithelial cells and macrophages, in vitro and ex vivo. Until recently, few studies have examined the internalization, trafficking, and fate of NTHI in host cells. It is important to clarify this interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 98 publications
0
107
0
Order By: Relevance
“…The costimulatory molecule CD161 is a key expression marker for MAIT cells, which can recognize the ligand lectin-like transcript 1 (LLT1) expressed by respiratory epithelial cells in response to infection and proinflammatory cytokines (48). H. influenzae can invade the lung tissue (49,50) and enter respiratory epithelial cells and macrophages in chronic bronchitis (6)(7)(8)51). Exacerbations of chronic bronchitis are associated with an increase in the presence of NTHi bacteria inside epithelial cells as seen in 33 to 87% of biopsies (6,8).…”
Section: Cd161mentioning
confidence: 99%
See 1 more Smart Citation
“…The costimulatory molecule CD161 is a key expression marker for MAIT cells, which can recognize the ligand lectin-like transcript 1 (LLT1) expressed by respiratory epithelial cells in response to infection and proinflammatory cytokines (48). H. influenzae can invade the lung tissue (49,50) and enter respiratory epithelial cells and macrophages in chronic bronchitis (6)(7)(8)51). Exacerbations of chronic bronchitis are associated with an increase in the presence of NTHi bacteria inside epithelial cells as seen in 33 to 87% of biopsies (6,8).…”
Section: Cd161mentioning
confidence: 99%
“…Nonencapsulated or nontypeable Haemophilus influenzae (NTHi) can be isolated in up to 80 to 87% of COPD exacerbations (5,6) and is the most common bacteria colonizing the airways in COPD (6), with colonization correlated with exacerbations, severity of airway inflammation (5), and symptoms (2,6). NTHi colonization is a major cause of tissue damage, and the bacteria can also invade the lung tissue, between epithelial cells and within macrophages (5,6), potentially facilitating immune evasion and persistence (7,8). NTHi colonization may induce airway inflammation through specific IgE-mediated hypersensitivity (9), through activation of innate immunity via Toll-like receptor (TLR)2/4, which leads to increased local production of IL-1b and IL-8 and reactive oxygen species, and through activation of adaptive immunity in which both B-and T-cell responses are implicated (6).…”
mentioning
confidence: 99%
“…Alum is still recognized as a substance, which is widely used in combination with diphtheria and tetanus toxoids and is the most reliable adjuvant for human consumption (35). Since new processes leading to the stimulation of lymphocytes and formation of memory cells are recognized, considerable efforts have been made to produce better adjuvants, particularly for T cell-mediated immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…pneumoniae and H. influenzae are the most common microbial agents of AOM in children. The prevalence of S. pneumoniae and H. influenzae in AOM is 19-74% and 16-61%, respectively [4]. A recent study demonstrated that H. influenzae infection may be responsible for persistent inflammation in the middle ear [3], and effective antimicrobial agents against H. influenzae make treating AOM of this etiology challenging.…”
Section: Discussionmentioning
confidence: 99%
“…This is partly explained by cell-invasive H. influenzae, which has recently been attracting attention. When H. influenzae organisms attach to and invade epithelial cells, these bacteria can escape both antimicrobial sterilization and the host immune response [4]. Because b-lactams do not penetrate cells well, they fail to come into contact with the bacteria and thus cannot exert their clinical effects.…”
Section: Introductionmentioning
confidence: 99%